Surgical criteria for femoroacetabular impingement syndrome: a scoping review. Issue 22 (20th February 2017) - Peters, Scott; Laing, Alisha; Emerson, Courtney; Mutchler, Kelsey; Joyce, Thomas; Thorborg, Kristian; Hölmich, Per; Reiman, Michael
Abstract : Background: The purpose of this review was to analyse and report criteria used for open and arthroscopic surgical treatment of femoroacetabular impingement syndrome (FAIS). Methods: A librarian-assisted computer search of Medline, CINAHL and Embase for studies related to criterion for FAIS surgery was used in this study. Inclusion criteria included studies with the primary purpose of surgery or surgical outcomes for treatment of FAIS with and without labral tear, and reporting criteria for FAIS surgery. Results: Diagnostic imaging was a criterion for surgery in 92% of the included studies, with alpha angle the most frequently reported (68% of studies) criterion. Reporting of symptoms was a criterion for surgery in 75%, and special tests a criterion in 70% of studies. Range-of-motion limitations were only a required criterion in 30%, only 12% of studies required intra-articular injection and 44% of studies described previously failed treatment (non-surgical or physiotherapist-led rehabilitation) as a criterion for surgery. Only 56% of included studies utilised the combination of symptoms, clinical signs and diagnostic imaging combined for diagnosis of FAIS as suggested by the Warwick Agreement on FAIS meeting. Conclusion: Diagnostic imaging evidence of FAIS was the most commonly reported criterion for surgery. Only 56% of included studies utilised the combination of symptoms, clinical signs and diagnostic imaging for diagnosis of FAIS as suggested by the Warwick Agreement on FAIS meeting, and only 44% of studies had failed non-surgical treatment (and 18% a failed trial of physiotherapy) as a criterion for surgery.